1969
DOI: 10.1128/jb.98.3.1307-1319.1969
|View full text |Cite
|
Sign up to set email alerts
|

Functions of F Pili in Mating-Pair Formation and Male Bacteriophage Infection Studied by Blending Spectra and Reappearance Kinetics

Abstract: The extent of removal at various blending speeds (blending spectrum) and the kinetics of reappearance after blending of the ability of male Escherichia coli bacteria to form mating pairs, to adsorb and be infected by ribonucleic acid male phage, and to adsorb and be infected by deoxyribonucleic male phage were identical to the blending spectrum and reappearance kinetics of microscopically visible F pili. The same results were obtained with an Hfr (high-frequency recombinant), F', or resistance transfer factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1969
1969
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…(The rate of specific pair formation is defined as the percentage increase in number of specific pairs per unit time in relation to the maximum number of specific pairs attained.) We believe, therefore, along with other investigators (2,18,28,29), that the ability to form specific pairs is solely dependent on the presence of F pili and, furthermore, that it is little affected by differences in F pili length and other cellular structures or by capabilities resulting from the various cultural conditions employed.…”
Section: Relationship Between Growth Conditions Of Donorsupporting
confidence: 62%
See 1 more Smart Citation
“…(The rate of specific pair formation is defined as the percentage increase in number of specific pairs per unit time in relation to the maximum number of specific pairs attained.) We believe, therefore, along with other investigators (2,18,28,29), that the ability to form specific pairs is solely dependent on the presence of F pili and, furthermore, that it is little affected by differences in F pili length and other cellular structures or by capabilities resulting from the various cultural conditions employed.…”
Section: Relationship Between Growth Conditions Of Donorsupporting
confidence: 62%
“…These three events must precede transfer of the donor chromosome during conjugation. After the discoveries that donor cells possess a donor-specific antigen (30) and are able to adsorb donor-specific ribonucleic acid (RNA) phages (24,25) to filamentous external structures (7) called F pili (4), it was demonstrated that these F pili are synthesized under the control of the fertility factor F (2)(3)(4) constitute the F-specific antigen (20), and are obligatory for specific pair formation (2,18,28,29). Brinton's group (2-4, 28, 29) and others (18,21,32) have further suggested that F pili may function as conjugation tubes in addition to their role in specific pair formation.…”
mentioning
confidence: 99%
“…Heated cells should also be useful for studying the reappearance of pili. Usually, blended cells that only produce about 60% of the control level of pili (3,12) are used to study reappearance (3,4,15,18,19). It might be better to use cells heated to 500C for this purpose, because they produce normal numbers of pili when the temperature is lowered to 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…MATERIALS AND METHODS Bacteria and bacteriophages. F pili were studied on a strain of E. coli K-12 (ERW) that is F+ His+/His- (15). R17, a spherical RNA phage, and M13, a filamentous DNA phage, were used to study donor-specific phage adsorption, and R17 was used to label pili for electron microscopy.…”
mentioning
confidence: 99%
“…The ability of a bacterial cell to act as a genetic donor is often correlated with the presence of sex pili on the cell surface (16). Most sex factors specify sex pili which belong to one of two main classes, F-like or I-like (14), but other classes have recently been observed (6).…”
mentioning
confidence: 99%